Exceptional localisation of an ectopic parathyroid adenoma at the level of the hyoid bone. (11th June 2014) - Musters, Linde; van Ginhoven, Tessa M; Smit, Casper
Abstract : Primary hyperparathyroidism is characterised by high parathyroid hormone (PTH) levels and concomitant hypercalcaemia. Ninety per cent is caused by solitary parathyroid adenomas, 10% by multiple adenomas, hyperplasia and carcinomas. Less than 0.1% of the inferior parathyroid glands are ectopically located. This case is of a 54-year-old woman with hypercalcaemia 3.05 mmol/L and high PTH 22 pmol/L. Scintigraphy and CT scan of the neck in 2009 showed no signs of ectopic tissue. After treatment with Aredia (pamidronate disodium) infusion, calcium decreased to 2.73 mmol/L. In 2010 the serum calcium levels increased again to 3 mmol/L. Repeated CT showed no ectopic tissue. However, revision of the CT by the multidisciplinary team including an experienced endocrine surgeon revealed an ectopic parathyroid gland at the level of the hyoid bone, which was surgically removed in 2011. Preoperatively the PTH level was 16.8 mmol/L, postoperatively it decreased to 2.9 mmol/L, proving a successful excision. In case of suspicion of a parathyroid adenoma a CT of the neck should be thoroughly assessed by a dedicated multidisciplinary team, including the head and neck surgeon, as clinical data and radiological findings must be combined since ectopic parathyroid adenomas are a rare entity. Thereafter the adenoma can be surgically removed and the patient cured.